Akuntabilitas Aset Sumber Daya Alam (Ekosistem Di Lahan Gambut) Dalam Kerangka Seea Di Kabupaten Kubu Raya Provinsi Kalimantan Barat - Elok Heniwati; Elisabeth Sedah (APSSAI ACCOUNTING REVIEW, 2026)
Research aims: This study analyzes the accountability of natural resource assets in peatland ecosystems within the framework of the System of Environmental-Economic Accounting – Ecosystem Accounting (SEEA EA). Design/Methodology/Approach: The study uses a qualitative case study of community agricultural activities in Kubu Raya Regency, West Kalimantan. Data were collected through in-depth interviews with farmers, government reports, agricultural statistics, and environmental documents. Data analysis used an interactive model based on the SEEA Ecosystem Accounting interpretive approach. Research findings: The results indicate that peatlands function as ecosystem assets that generate various ecosystem services, particularly provisioning services, such as agricultural produce serving as a source of community income. Existing accountability patterns remain dominated by program reporting and budget utilization, and information about the condition of peat assets, ecosystem services, and environmental benefits has not been systematically integrated. Theoretical contribution/Originality: This study proposes the concept of ecological accountability as a form of public accountability that positions the condition of ecological assets, ecosystem services, and natural resource sustainability as integral components of the accountability system. The findings reinforce the relevance of implementing SEEA Ecosystem Accounting to support peatland management that is more transparent, sustainable, and oriented toward community well-being.